A photochromic and scintillation Eu-MOF with visual X-ray detection in bright and dark environments. Issue 25 (9th March 2022) - Sun, Yu-He; Li, Chun-Lei; Wang, Wen-Fei; Wang, Shuai-Hua; Li, Pei-Xin; Guo, Guo-Cong
Abstract : A rare earth MOF with both X-ray induced photochromic and scintillation properties is reported. The two functions all arise from the highly effective X-ray absorption and can be used for simple X-ray detection in different environments. Abstract : The detection of X-rays has always been a frontier of scientific research. An Eu-MOF with both X-ray-induced photochromic and scintillation properties has been synthesized through the combination of a photochromism-active viologen ligand and rare earth Eu element with high-efficiency absorption of X-rays. In a bright environment, Eu-MOF exhibits different color changes under high-energy X-rays and low-energy X-rays, which can effectively distinguish X-rays. Eu-MOF can also be used for X-ray detection by scintillation properties in dark environments. This work provides a new perspective on the design of multifunctional materials that can perform simple X-ray detection in different environments.